Analisis Motivasi Wirausaha Coffe Shop di Kota Kendari - Dwi Paksi, Yoga; Asriani; Syamsinar (Agrisurya, 2024)
The growth of coffee shops in Kendari City has increased significantly in recent years, driven by the high demand for places to relax and gather socially. This research aims to analyze the entrepreneurial motivation of Coffee Shops in Kendari City. Using a qualitative approach, data was obtained through interviews with Coffee Shop owners and managers as well as observations of their business operations. The results of the research show that economic motivation and social motivation in Coffee Shop entrepreneurship each obtained a total average score of 2.33 in the high category, while affiliate motivation obtained a total average score of 2.67 in the high category. Coffee shop entrepreneurship in the city of Kendari as a whole is in the high motivation category and has the opportunity to be developed Keywords: motivation, entrepreneurship, Coffee Shop, Kendari City